Nurturing Student Self-Awareness in Pesantren Education: Institutional Strategies and Their Impacts at Al-Amien Tegal Islamic Boarding School - Muhlishah, Atiqatul; Riadi, Dedi Eko (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2024)
Islamic boarding school education in Indonesia faces a persistent challenge in cultivating santri engagement that is genuinely intrinsically motivated rather than driven by external enforcement alone. This study investigates the institutional strategies employed by Pondok Pesantren Al-Amien Tegal Prenduan to nurture self-awareness among its santri as the motivational foundation for their participation in pesantren activities. Employing a qualitative descriptive approach through case study design, data were collected through in-depth interviews with key institutional informants — including teaching staff, organizational administrators, and santri — complemented by direct observation and documentary analysis. Data were analyzed through three sequential stages of data reduction, data display, and conclusion drawing. The findings reveal that the institution implements five interconnected strategies: disciplined habituation, exemplary leadership, organizational participation through OSPA, structured reflection sessions, and extracurricular engagement. Santri self-awareness exists along a developmental continuum shaped by age, educational level, and length of institutional residence, progressing from externally oriented compliance toward genuinely internalized value-based engagement. The impacts of these strategies are observable across personal, spiritual, and social dimensions of santri participation in institutional life. This study concludes that self-awareness development in pesantren education is fundamentally a relational and communal achievement, one that demands deliberate institutional investment across every dimension of santri daily experience.